Escherichia coli kgtP encodes an alpha-ketoglutarate transporter. - Seol, W (1991)
The witA gene located between pss and rrnG on the Escherichia coli chromosome encodes a 432-amino acid protein. It is homologous to a human hepatoma glucose transporter and to E. coli membrane proteins that transport citrate (CitA), arabinose (AraE), and xylose (XylE), and, like these carrier proteins, WitA also contains 12 highly hydrophobic putative membrane-spanning regions. Gene disruption mutants constructed in two E. coli strains grew slowly or not at all, depending on genetic background, in M9 minimal medium containing alpha-ketoglutarate. Growth on alpha-ketoglutarate and uptake of alpha-[14C]ketoglutarate were restored by transformation with plasmids containing witA. These complementation studies indicate that WitA is an alpha-ketoglutarate transporter and should be renamed kgtP(alpha-ketoglutarate permease).